A realistic evaluation of two aggression management training programmes - Linsley, Paul (2013)
Whilst the training of healthcare staff is seen as a key element to the prevention and management of violence and aggression, questions remain as to the effectiveness of these programmes in preparing staff to apply this to clinical practice. To date there is a relative paucity of well-designed studies into the effectiveness of the training to prevent and manage violence and aggression in healthcare settings. Within this context a study was conceived to examine the effectiveness of two aggression management training programmes in preparing staff for clinical practice.